A Decade of Declining Earnings Inequality in the Russian Federation - Calvo, Paula Andrea; Lopez-Calva, Luis-Felipe; Posadas, Josefina (World Bank, Washington, DC, 2015)
Wage inequality decreased significantly in the Russian Federation over the 2000s. The economic expansion experienced throughout the decade led to an improvement in social indicators, with a large reduction in poverty rates and an increase in higher education. In this context, wage inequality showed a sharp decline, with the Gini index on labor income decreasing by 18 percent between 2002 and 2012. Using data from the Russian Longitudinal Monitoring Survey, this paper documents the reduction in wage inequality and explores potential factors behind the trend. The analysis uses a decomposition technique proposed by Fortin, Lemieux, and Firpo (2011) to disentangle the main drivers behind changes in the wage distribution. The results suggest that wage structure effects are more important than composition effects for explaining changes in wage inequality. Institutional factors, such as minimum wage policies and changes in the returns to employment in different sectors and types of firms as well as the reduction of the skill premium, emerge as the most relevant factors for explaining changes in the wage structure.